Fluctuating effects of genetic and plastic changes in body mass on population dynamics in a large herbivore. Issue 9 (2nd August 2017) - Pigeon, Gabriel; Ezard, Thomas H. G.; Festa‐Bianchet, Marco; Coltman, David W.; Pelletier, Fanie
Abstract: Recent studies suggest that evolutionary changes can occur on a contemporary time scale. Hence, evolution can influence ecology and vice‐versa. To understand the importance of eco‐evolutionary dynamics in population dynamics, we must quantify the relative contribution of ecological and evolutionary changes to population growth and other ecological processes. To date, however, most eco‐evolutionary dynamics studies have not partitioned the relative contribution of plastic and evolutionary changes in traits on population, community, and ecosystem processes. Here, we quantify the effects of heritable and non‐heritable changes in body mass distribution on survival, recruitment, and population growth in wild bighorn sheep ( Ovis canadensis ) and compare their importance to the effects of changes in age structure, population density, and weather. We applied a combination of a pedigree‐based quantitative genetics model, statistical analyses of demography, and a new statistical decomposition technique, the Geber method, to a long‐term data set of bighorn sheep on Ram Mountain (Canada), monitored individually from 1975 to 2012. We show three main results: (1) The relative importance of heritable change in mass, non‐heritable change in mass, age structure, density, and climate on population growth rate changed substantially over time. (2) An increase in body mass was accompanied by an increase in population growth through higher survival and recruitment rate. (3) Over the entire study period, changes in the body mass distribution of ewes, mostly through non‐heritable changes, affected population growth to a similar extent as changes in age structure or in density. The importance of evolutionary changes was small compared to that of other drivers of changes in population growth but increased with time as evolutionary changes accumulated. Evolutionary changes became increasingly important for population growth as the length of the study period considered increased. Our results highlight the complex ways in which ecological and evolutionary changes can affect population dynamics and illustrate the large potential effect of trait changes on population processes.